Digital Constitutionalism and the Future of Human Rights: A Comparative Review - Teravosa, Gillan; Nagari, Sulthon Bangun (Legalis : Journal of Law Review, 2025)
This study presents a comprehensive narrative review of the evolving relationship between constitutionalism and the protection of human rights in various global contexts. The primary aim is to explore how constitutional frameworks adapt to contemporary challenges and uphold human rights amid increasing political complexity and technological transformation. A rigorous literature search was conducted using databases such as Scopus, Web of Science, and Google Scholar with keywords including "constitutionalism," "human rights evolution," "rule of law," "limited government," and "comparative constitutional law." The review synthesized findings from comparative legal studies, case law analysis, and theoretical literature. The results indicate a growing reliance on constitutional courts to safeguard fundamental rights, especially in jurisdictions like Germany, Poland, and Colombia. However, systemic barriers such as weak institutions and political interference continue to challenge effective constitutional implementation. Regional differences further complicate the picture, with the EU promoting supranational human rights standards, while Latin America advances progressive constitutional reforms, and parts of the Islamic world grapple with integrating Sharia principles. The emergence of digital constitutionalism adds a new dimension to this discourse, calling for regulatory frameworks that protect digital rights. Civil society’s role is increasingly significant in shaping these legal evolutions. In conclusion, reinforcing judicial independence, integrating global legal norms, and fostering public awareness are critical to strengthening constitutionalism. Future research should prioritize the impact of digital governance and transnational jurisprudence on human rights.